Serum-Free T3 and T4 Hormone Levels and Their Association with Severity of Traumatic Injuries: A Retrospective Observational Study - Ajagallay, Sarita; Mane, Shobhita K.; Singh, Gambheer (Achievements and Challenges of Medicine and Medical Science Vol. 5, 2024)
Background: Serum thyroid hormone levels are extensively explored in trauma victims for severity of trauma and mortality of patients, especially in patients with severe traumatic brain injury. There is a scarcity of such studies for trauma to other parts of body systems or Polytrauma. The objective of the current study is to investigate the association of Serum-Free T3 and T4 hormones in patients with severe traumatic injury. Methods: The Retrospective observational study was conducted at the Department of General Surgery, Pt. J.N.M. Medical College & Associated Dr. B.R. Ambedkar Memorial Hospital, Raipur, C.G. Total 77 patients were included in the study. Here, 68 (88.31 %) were males and 9 (11.68 %) were female patients. The patients with head, chest and abdominal trauma who sustained their injuries within 24 hours of admission, within the age group of 10-82 years were included. The levels of Free Thyroid hormones (FT3 and FT4) at admission, after 24 hrs and on 5th day of admission were evaluated. Results: On admission, the mean serum-free T3 in patients included in this study was 1.51 pmol/l (SD=0.18). After 24 hrs and on 5th day, mean FT3 was 1.47 pmol/l (SD = 0.14). The mean serum-free T4 value on admission, after 24 hrs and on 5th day was 0.71 pmol/l (SD=0.52). Till the 5th day of assessment, 14 patients were discharged while 12 died in the course of treatment. No statistically significant association between FT3 levels and outcome could be seen (p=0.672). Similarly, no overall significant association for FT4 levels with outcome was observed (p=0.627). However, in 9 out of 12 patients who died, deranged FT4 level was found (75 %). Although the mean value for serum FT4 at admission, at 24 hours and after 5th day was within normal limit, the measured individual serum FT4 levels were reduced in the patients according to the severity of trauma. Conclusions: The role of hormone level in the prediction of outcomes in trauma victims has important mechanisms that remain an unexplored subject. The deranged FT4 levels have a significant association with the severity of trauma. The prediction of the status FT3 and FT4 levels of the patients paves the way for exploring the methods in the future which could be of clinical use for the patient’s management.